Acquired, Idiopathic, Patterned Facial Pigmentation (AIPFP) including periorbital pigmentation and pigmentary demarcation lines on face follows the Lines of Blaschko on face - Nilendu Sarma; Sayantani Chakraborty; Sneha Ranjan Bhattacharya (Wolters Kluwer Medknow Publications, 2014)
Background: Acquired, non-nevoid, apparently idiopathic facial pigmentation are distributed over some specific locations like periorbital area, zygomatic area, malar area, root of nose, perioral and mandibular area. Periorbital pigmentation is the most well known entity in this group. These are bilaterally distributed homogenously diffuse gray to dark gray or slate-gray colored patches showing progressive intensification of pigmentation. These are often considered as physiologic or constitutional pigmentation. Some portions of the margins of these patches were described previously as pigmentary demarcation line (PDL- F, G, H). Aim : To analyze the distributional patterns of acquired, apparently idiopathic facial pigmentations and to evaluate the etiologic aspects of these conditions. Materials and Methods: Spatial patterns, distribution, and orientation were analyzed among 187 individuals with idiopathic non-nevoid, facial pigmentation. Observed patterns were compared with various pigmentary nevi and Blaschko's lines on face. Results: It was found that most of the idiopathic facial pigmentary alterations including periorbital pigmentation and PDL on face had specific patterned distribution that had high similarity to that of the pigmentary nevi and Blaschko's lines on face. Conclusion: It is hypothesized here that phenotypic expression of acquired patterned pigmentation (AIFPFP) is due to genetically determined increased pigmentary functional activity to various known and unknown yet natural factors like UV rays and aging. Mosaicism is a definite possibility. We also consider that these patterns actually reflect the normal patterns of embryological human pigmentation on face.